The Students Ability in Using Countable and Uncountable Nouns: at Second Year Students of SMPN 1 Aikmel in East Lombok - M Junaidi (Jurnal Ilmiah Telaah, 2021)
Abstrak: Penelitian ini bertujuan untuk mengetahuai kemampuan siswa dalam menggunakan Countable dan Uncountable nouns  kelas 2 di SMPN 1 Aikmel. Jumlah populasi dari penelitian ini adalah 280 siswa, sample 28 siswa atau 10% dari populasi yang ada. Instrument yang di gunakan pada penelitian ini multiple-choice atau pilihan ganda untuk mengetahui kemampuan siswa dalam menggunakan countable dan completions atau melengkapi yang di gunakan untuk mengetahui kemampuan siswa dalam grammar . adapun langkah- langkah yang di gunakan guru dalam pembelajaran countable dan uncountable nouns adalah latihan . berdasarkan hasil data yang di dapat dalam pilihan ganda adalah 1 orang mendapat 100 (3,6%) dan 2 orang mendapat 50 (10,8).itu artinya siswa SMPN 1 Aikmel dikatakan berhasil dalam menggunakan countable and uncountable noun in teaching grammar especially in learning english. Adapun siswa yang menggunakan melengkapi test adalah 2 orang siswa mendapat 100(3,6%) dan 1 orang mendapat 40 (7,2%).Abstract: This study is intended to find out The students’ ability in using countable and uncountable nouns at second year students of SMPN 1 Aikmel academic year 2010/2011. This is aimed at finding out The students’ ability in using countable and uncountable nouns. The population of this study was all of the second grade students of SMPN 1 Aikmel which consist of 280 students. And the sample of this study is 28 or 10 % from population. The instrument consists of sentences namely building with countable and uncountable noun and practice in sentence. The test is divided into two parts namely multiple- Choice test and completion in grammar  test in given after the students have the treatment of teaching from current English teacher to measure the students’ ability in using countable and uncountable noun. From the result of previous discussion, it is clear enough to conclude that the result for multiple- choice test, there are 1 achieve 100 (3,6 %), 1 students achieve 90 (3,6 %), 6 students achieve 80 (21,6 %), 10 students achieve 70 (36 %), 3 students achieve 60 (25,5 %), 3 students achieve 50 (10,8 %); that means, mostly students have good enough knowledge about countable and uncountable nouns. In completion test there are 2 students achieve 100 (7,2 %), 3 students achieve 90 (10,8 %), 3 students achieve 80 (10,8 %), 7 students achieve 70 (25,2 %), 5 students achieve 60 (18%), 6 students achieve 50 (21,6 % ) and the last 2 students achieve 40 (7,2 %). This also means that researcher found the students ‘ mastery about countable and uncountable noun good enough.